Customary-Based Waqf Practices: Exploring Socio-Economic Empowerment and Development Models in The Tana Luwu Indigenous Community - Achmad Syam, Andi; Fiqran, Muh. Fiqran; Abdullah, Muh. Ruslan; Karina, Mutiara (Filantropi : Jurnal Manajemen Zakat dan Wakaf, 2025)
This article deals with the development of customary waqf in the socio-economic empowerment of indigenous peoples. This study aims to analyze the potential of customary waqf in the Tana Luwu community, evaluate its role in socio-economic empowerment, and formulate a model for the development of customary waqf that can be implemented sustainably. This study uses a qualitative approach with an exploratory-descriptive study design using case study and Participatory Action Research (PAR) methods that focus on indigenous communities as the main subjects to explore customary waqf practices in Tana Luwu. The results show that customary practices such as customary land management, traditional granaries, mutual assistance, and tongkonan are indeed in line with the values of waqf redistribution. However, without institutional reform and adequate legal protection, these practices are prone to fragmentation. Therefore, the development of waqf in indigenous communities can be carried out by making Indigenous Institutions the collective nazhir to manage customary land, traditional granaries, and traditional facilities. In addition, a participatory approach must be accompanied by waqf education and literacy tailored to the local context.